Papillary ependymoma of the endometrium. Issue 6 (30th October 2014) - Schuldt, Maolly; Retamero, Juan A; Bergeron, Christine; Nogales, Francisco F
<x xml:space="preserve">Abstract</x> Aims To report an exceptional case of papillary ependymoma occurring in the endometrium. Methods and results A clinicopathological study was performed regarding a case of papillary ependymoma occurring in the endometrial cavity of a 61‐year‐old patient who had presented with a solid‐type, stage III anaplastic ependymoma of the ovary, treated with cytoreductive surgery that included total abdominal hysterectomy. The uterus was enlarged and showed a dilated cavity, with broadly implanted papillary excrescences without myometrial invasion that were covered by tall, cylindrical cells. These cells had glial fibrillary acidic protein‐expressing cytoplasm that was also positive for cytokeratins 7, 8, 18, and 34β‐E12, epithelial membrane antigen, S100 protein, vimentin, and oestrogen and progesterone receptors. Conclusions Pathogenetically, the presence of this uterine ependymoma could represent either an example of multicentricity or a phenomenon of transtubal implantation of the ovarian tumour. Exceptionally, papillary ependymoma can occur in the endometrium, and may prompt differential diagnoses with other papillary endometrial tumours. Pathologists should consider this rare possibility in the differential diagnosis of papillary ovarian and endometrial lesions.